NATURAL RADIOACTIVITY OF GRANITES USED AS BUILDING MATERIALS IN GREECE - Pavlidou, S.; Koroneos, A.; Papastefanou, C.; Christofides, G.; Stoulos, S.; Vavelides, M. (Bulletin of the Geological Society of Greece, 2004)
The granites used in Greece as building materials and imported from foreign countries, mainly from Spain and Brazil, are rock types similar with the stony building materials world-wide used. Sixteen kinds of different granites, considered as the most popular, were sampled and their natural radioactivity was measured by gamma spectrometry. The, 226Ra, 232Th and 40K contents of granites were compared to corresponding ones of other building materials as well as other granite types used all over the world. For the reasons of radiological impact from use of granites as building materials, the absorbed dose and the effective dose as well were determined. Although the annual effective dose is higher than the limit of 1 mSv a"1 for some granites examined, they could be used safely as building materials, considering that their contribution in most of the house constructions is very low. An attempt to correlate the relatively high level of natural radioactivity of different kinds of granites with the presence of radioactive minerals and their chemical composition was also made.